Associations of childhood maltreatment with subsequent illicit drug use among Chinese adolescents: The moderating role of the child's sex. (November 2018) - Guo, Lan; Li, Pengsheng; Pan, Siyuan; Li, Ming; Li, Wuquan; Gao, Xue; Huang, Guoliang; Xu, Yan; Lu, Ciyong
Highlights: Childhood maltreatment is positively associated with illicit drug use. Child's sex plays a moderating role in the aforementioned associations. Sexual abuse is more strongly associated with illicit drug use than other forms of maltreatment. Abstract: Adolescence is a critical period for the onset of illicit drug use. This study aimed to estimate the prevalence of illicit drug use among Chinese adolescents, to assess the associations between different forms of childhood maltreatment and subsequent illicit drug use and to test whether the child's sex plays a moderating role in the associations. A secondary analysis was made of cross-sectional data collected from 10th to 12th graders from China who were sampled in the 2015 School-based Chinese Adolescents Health Survey. A total of 59, 518 questionnaires were included in the final analysis. The prevalence estimates and logistic regression analyses were weighted to account for the complex survey design. If the interaction term (between childhood maltreatment and sex) was significantly associated with illicit drug use, we would perform stratification analyses across sex. Of the total sample, 45.2% were boys, and the mean (SD) age was 17.0 (0.9) years. The results of stratification analyses demonstrated that among boys, physical abuse and sexual abuse were independently associated with an increased risk of use during their lifetime of MDMA, methamphetamine, ketamine, and mephedrone; among girls, only emotional abuse and sexual abuse were associated with MDMA use, methamphetamine use, ketamine use, and mephedrone use.